1994
DOI: 10.1063/1.466425
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the structure and dynamics of liquid water at hydrophobic and hydrophilic surfaces—a molecular dynamics simulation study

Abstract: The structure and dynamics of liquid water at the interface with three solid surfaces has been investigated via molecular dynamics simulation. The three surfaces include a flat hydrophobic surface, an atomically rough hydrophobic surface, and a contrasting, hydrophilic, fully hydroxylated silica surface. The results of analysis show that, as expected, the solvent near each of the two hydrophobic surfaces behaves essentially equivalently, with loss of hydrogen bonding at the interface. For the hydroxylated surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
603
4
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(675 citation statements)
references
References 32 publications
66
603
4
2
Order By: Relevance
“…The hindered mobility of water molecules confined by hydrophilic surfaces (k ) 1.0) has been observed with similar confining surfaces and was attributed to the strong HB interactions between water and surface silanol groups. 29 The slow translational dynamics observed at k ) 0.0, however, seems counterintuitive at first sight given the comparatively weaker water-substrate interactions. Fast interfacial dynamics have been observed for TIP4P and TIP5P water 29,47 and for a Lennard-Jones fluid 48 confined by perfectly flat hydrophobic surfaces, while the dynamics of a Lennard-Jones fluid confined by a rough hydrophobic surface appear to slow down.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hindered mobility of water molecules confined by hydrophilic surfaces (k ) 1.0) has been observed with similar confining surfaces and was attributed to the strong HB interactions between water and surface silanol groups. 29 The slow translational dynamics observed at k ) 0.0, however, seems counterintuitive at first sight given the comparatively weaker water-substrate interactions. Fast interfacial dynamics have been observed for TIP4P and TIP5P water 29,47 and for a Lennard-Jones fluid 48 confined by perfectly flat hydrophobic surfaces, while the dynamics of a Lennard-Jones fluid confined by a rough hydrophobic surface appear to slow down.…”
Section: Resultsmentioning
confidence: 99%
“…43 Nevertheless, we choose to model the metastable -cristobalite phase because an accurate force field for this type of surface has been developed previously. 29 As part of an ongoing research effort we plan to investigate the effects of changing the surface structure to that of the stable phase, R-cristobalite, in addition to amorphous silica and silica gels; as well as the inclusion of surface defects, which have been shown to affect water adsorption. 44 We will also study the effect of substrate flexibility (vide infra).…”
Section: Simulation and Computational Detailsmentioning
confidence: 99%
“…The parameters C 9 and C 3 are those chosen for the interaction between a water molecule and a "hydrophobic" solid surface. 5 The potential function v͑z͒ is zero at the distance z 0 = ͑C 9 / C 3 ͒ 1/6 = 2.47 Å and rapidly increases at shorter distances. In Fig.…”
Section: System and Conditionsmentioning
confidence: 99%
“…There are many computational studies on confined water, [4][5][6][7][8][9][10][11][12] some of the pioneering works date back to 1980s. 4 One of the earlier computer simulations focusing on liquidsolid phase transitions 13 showed that water between hydrophobic surfaces freezes into a bilayer form of crystalline ice when temperature is lowered under a fixed normal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In bio-mimicking systems such as in micelles, reverse micelles, the structure and dynamics of water were also investigated [22][23][24]. Beside experiments, computer simulation also aids to understand the interfacial properties of water molecules [25,26]. The orientation and polarization of the interfacial water [27][28][29][30][31][32], water conductance through carbon nanotube [33], the hydrogen bonding structure of water and of the lipid headgroups has also been assessed [32,34,35] using MD simulations.…”
Section: Introductionmentioning
confidence: 99%